2022
DOI: 10.1101/2022.01.10.475153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of methods incorporating biological function and GWAS summary statistics to accelerate discovery

Abstract: Where sufficiently large genome-wide association study (GWAS) samples are not currently available or feasible, methods that leverage increasing knowledge of the biological function of variants may illuminate discoveries without increasing sample size. We comprehensively evaluated 18 functional weighting methods for identifying novel associations. We assessed the performance of these methods using published results from multiple GWAS waves across each of five complex traits. Although no method achieved both hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…While machine learning out-performed individual methods and even linear combinations of methods, it only correctly identified an additional 1-8 genes, and only for highly heritable traits with a well-powered smaller GWAS (SCZ and ICV). This observation converges with related work evaluating methods for SNP and locus annotation (13,14,48), which has concluded that such methods can only marginally increase the number of true-positive observations. Similarly, prior work examining positional gene-based methods in a simulated trait with relatively few causal SNPs (n=602) observed a tradeoff between sensitivity and specificity (49), which is also seen here.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…While machine learning out-performed individual methods and even linear combinations of methods, it only correctly identified an additional 1-8 genes, and only for highly heritable traits with a well-powered smaller GWAS (SCZ and ICV). This observation converges with related work evaluating methods for SNP and locus annotation (13,14,48), which has concluded that such methods can only marginally increase the number of true-positive observations. Similarly, prior work examining positional gene-based methods in a simulated trait with relatively few causal SNPs (n=602) observed a tradeoff between sensitivity and specificity (49), which is also seen here.…”
Section: Discussionsupporting
confidence: 88%
“…The gene-level focus reflects an additional weakness of the omics-integration approach, in that it could lead to improved knowledge of biology without narrowing down the identity of causal loci in human populations. Thus, while recent related studies using locus-level analyses yielded similar findings (14), we cannot rule out that alternative methods could have led to stronger results. We note some additional limitations of the present study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…15,16 Some have speculated that multi-omics could serve as a substitute for additional sample size, and "recover" true signal from smaller GWAS by increasing support for signals that do not meet criteria for genome-wide significance. [17][18][19] This is an appealing proposition, because it would reduce the need (and expense) for collection and phenotyping of larger samples. Some early work using expressionbased methods (e.g., transcriptome-wise association analyses -TWAS) found that they can identify genes that would eventually achieve genome-wide significance in subsequent, larger GWAS, 20,21 although these studies did not evaluate what proportion of all novel genes were first identified by TWAS.…”
Section: Introductionmentioning
confidence: 99%